Estetika Material Bambu dalam Arsitektur Kontemporer: Sinergi antara Kekuatan Struktur dan Keindahan Visual - Imam romadhoni; Mukhammad Alwi Athoillah (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to construct an integrative model of the relationship between the structural performance and visual aesthetics of bamboo in contemporary architecture through a non-empirical conceptual-analytical approach. The methods employed include systematic interpretive synthesis combined with concept mapping to identify causal relationships between the mechanical strength of bamboo and variables related to the perception of spatial aesthetics. The findings indicate that bamboo possesses structural characteristics such as high flexibility, an optimal strength-to-weight ratio, and joint stability that is adaptable to modern construction systems. Aesthetically, bamboo shapes the spatial experience through transparency, structural rhythm, and natural textures that enhance users’ visual perception of the space. The integration of digital technology and an architectural ecology approach expands bamboo’s function as an active material that contributes to structural efficiency and environmental sustainability. The resulting conceptual model affirms the interdependence between technical and aesthetic aspects within a single architectural system. Bamboo is positioned as a strategic material in the development of a sustainable architectural paradigm that combines technological innovation, structural strength, and the aesthetic experience of space.